BUDAYA HUMA BETANG MASYARAKAT DAYAK KALIMANTAN TENGAH DALAM GLOBALISASI: TELAAH KONSTRUKSI SOSIAL - Suwarno Suwarno (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This paper is an antropological review on Dayak tradition of Huma Betang, a traditional house for Dayak community in Central Kalimantan. Huma betang or betang has a length of 30-150 meters, 10-30 meters wide and 3-5 meter high. The building uses high quality iron wood, can stand up to hundreds of years as well as anti-termite. It used to be inhabited by 100-150 people, inhabited by one big family and headed by a Pambakas Lewu. Studies on people's living in Betang Damang Tumbang Anoi Gunung Mas found several cultural values of Betang Dayak community: (1) hapsari, (2) handep, (3) belom bahadat, and (4) hapakat kula.  Hapahari is defined as a brotherhood and togetherness in life betang.  Handep is mutual help, pandohop (aid), mutual mandohop (help).  Belom bahadat (live civilized and ethical) is a rule or etiquette that govern life together, that appreciate the prevailing custom in the territories of indigenous communities concerned.  Hapakat kula (mutually agree) is a hallmark of life of the inhabitants betang. Occupants of betang held deliberations in any activities of common interest of tradition betang inhabitants since centuries ago.